(untitled) (Physical Education, Health and Social Sciences, 2025)
The review investigates healthcare applications of data analytics that demonstrate potential to create substantial changes toward improved healthcare delivery with better patient outcomes. The healthcare industry implements data analytics as its essential tool to address current rising problems including cost growth beside resource constraints and uneven medical service availability. Healthcare organizations use advanced analytical approaches to obtain practical insights from extensive datasets which enables better evidence-based decisions and better resource utilization decisions. This review examines multiple data analytics applications ranging from Electronic Health Records (EHR) examination to Clinical Decision Support Systems (CDSS) functionality as well as predictive patient diagnosis systems and personal medicine delivery systems and patient engagement solutions. The applications showcase the extensive advantages of data-led solutions because they advance treatment precision and boost medical outcomes while delivering individualized healthcare approaches to patients. The review gives coverage to the practical obstacles healthcare faces when merging data analytics with healthcare yet it arrives at substantial advancements made through data analysis in medicine. Healthcare analytics demonstrates a promising future because artificial intelligence alongside wearable technology and blockchain systems will drive additional healthcare service improvements. This study establishes fundamental knowledge for future analytical studies of healthcare data analytics while it supports evidence-based medical approaches to create global improvements in patient care through policy recommendations.